Pesantren and Social Empowerment: A Critical Analysis On Pesantren Al-Imdad Yogyakarta And Pesantren Maslakul Huda Central Java - Widayanti, Sri (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Poverty and social problems give rise to many different perspectives and analyzes related to the causative factors and their complexity. These differences have an impact on different social interventions conducted by various parties, including among pesantren in Indonesia. Using qualitative method, this study explores the perspectives and analysis of pesantren on poverty and community empowerment in two pesantrens organizing socio-economic empowerment programs for subordinate groups namely Pesantren Al-Imdad in Yogyakarta and Pesantren Maslakul Huda in Central Java. This research results in three types of analysis, i.e. conventional, semi-progressive and progressive. The conventional analysis defines poverty as community’s inability to meet their basic needs, caused by their own mistakes of not having skills and enterpreneurship so that empowerment is viewed as a tool to direct the community in accordance with the pesantren’s decisions of empowerment programs. The semi-progressive analysis defines poverty as a multidimenstional problem, caused by structural and human factors so that empowerment is viewed as a strategy to increase the capacity of community and pesantren. The progressive analysis defines poverty as multidimentional problem, caused by structural factors and community is seen as a victim of unjust system so that empowerment is viewed as pesantren's alignments to subordinate groups by organizing joint forces to fight for the rights and interests of the community.